Role of leucine in protein metabolism during exercise and recovery - Layman, D. K. (Canadian Journal of Applied Physiology, 2002)
Exercise produces changes in protein and amino acid metabolism. These changes include degradation of the branched-chain amino acids, production of alanine and glutamine, and changes in protein turnover. One of the amino acid most affected by exercise is the branched-chain amino acid leucine. Recently, there has been an increased understanding of the role of leucine in metabolic regulations and remarkable new findings about the role of leucine in intracellular signaling. Leucine appears to exert a synergistic role with insulin as a regulatory factor in the insulin/ phosphatidylinositol-3 kinase (PI3-K) signal cascade. Insulin serves to activate the signal pathway, while leucine is essential to enhance or amplify the signal for protein synthesis at the level of peptide initiation. Studies feeding amino acids or leucine soon after exercise suggest that post-exercise consumption of amino acids stimulates recovery of muscle protein synthesis via translation regulations. This review focuses on the unique roles of leucine in amino acid metabolism in skeletal muscle during and after exercise.